Subacute herpes simplex virus type 1 encephalitis: a case report - Maria Lypiridou; Konstantinos Kalafatakis; Kyriaki Astara; Anna Margoni; Eleftheria Karakatsani; Georgios Stouraitis (Encephalitis, 2025)
Herpes simplex encephalitis (HSE) is a potentially fatal infection of the brain parenchyma with high mortality rates when left untreated. It typically affects the medial temporal lobe, and patients commonly present with headache, fever, and altered mental status. The combination of clinical findings and brain imaging should raise suspicion, whereas cerebrospinal fluid (CSF) analysis should establish the diagnosis. In a few cases, HSE presents with subacute progression, making diagnosis more challenging. Treatment with acyclovir should begin immediately after HSE is suspected; otherwise, the mortality rate is high. Herein, we present a rare case of HSE with a subacute course admitted to the emergency department because of an episode of syncope with concomitant bradycardia. HSE symptoms developed gradually during the first week after hospitalization. Typical imaging findings, CSF analysis, and polymerase chain reaction results positive for herpes simplex virus-1 confirmed a diagnosis of HSE. The insidious symptomatology of this case led to delayed acyclovir administration and the patient unfortunately died 4 days after diagnosis.